2010
DOI: 10.1111/j.1600-0609.2010.01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for non‐functional Dickkopf‐1 (DKK‐1) signaling in chronic lymphocytic leukemia (CLL)

Abstract: For the first time we show the expression of DKK1 in CLL cells. Unlike in similar tumors, the addition of DKK1 to culture of CLL cells does not inactivate WNT pathway. The reason for this could be the absence of the binding domain of LRP6. On the other hand, a truncated LRP6 without extracellular DKK1 binding domain could lead to an uncontrollable activation of WNT signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Therefore, two pairs of primers were selected to examine the mRNA expression of LRP6: one for the extracellular domain of LRP6, responsible for DKK1 binding, and another for the intracellular region, essential for inhibiting GSK3β [22]. Of great note, neither the extracellular domain nor the intracellular domain of LRP6 were changed, although the expression of β-catenin was dramatically altered upon DKK1 up-regulation (Figure 6A) or knockdown (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, two pairs of primers were selected to examine the mRNA expression of LRP6: one for the extracellular domain of LRP6, responsible for DKK1 binding, and another for the intracellular region, essential for inhibiting GSK3β [22]. Of great note, neither the extracellular domain nor the intracellular domain of LRP6 were changed, although the expression of β-catenin was dramatically altered upon DKK1 up-regulation (Figure 6A) or knockdown (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…LRP6 expression has been detected in primary CLL cells, albeit at low levels (22,23). As salinomycin could block Wnt-induced LRP6 phosphorylation and cause the degradation of LRP6 protein in HEK293 cells (Fig.…”
Section: Effects Of Salinomycin On Different Components Of Wnt Signalingmentioning
confidence: 87%
“…It has been demonstrated that the Wnt signaling pathway is activated in CLL cells and that uncontrolled Wnt/ β -catenin signaling may contribute to the defect in apoptosis that characterizes this malignancy [30]. It is thought to be responsible for the extended survival of CLL cells in vivo [31]. In primary CLL cells, Wnt proteins are overexpressed, and physiological inhibitors of this pathway are inactivated [32].…”
Section: Wnt Signaling In Cancer and Chronic Leukemiamentioning
confidence: 99%
“…Normal B cells proved to have significantly higher levels of extracellular, DKK1-binding domain of LRP6. On the other hand, a truncated LRP6 without extracellular DKK1-binding domain could lead to an uncontrollable activation of Wnt signaling in CLL [31]. …”
Section: Wnt Signaling In Cancer and Chronic Leukemiamentioning
confidence: 99%